2021
DOI: 10.3390/ijgi10090582
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Pattern of Population Mobility during the Spring Festival in the Yangtze River Delta Based on Complex Network Analysis: An Empirical Analysis of “Tencent Migration” Big Data

Abstract: Population mobility patterns are an important reflection of the future distribution of migrant populations and the evolution trends of urbanization patterns. However, although research based on statistical data can reveal the pattern of population flow, it also shows a time lag. Most of the population flow network research based on location services data has failed to fully discuss the symmetry of directional outflows and inflows in the same place and the two-way symmetrical connections between places. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…It is vital in promoting coordinated regional development and participating in international cooperation and competition. However, there are still some problems in urban agglomerations in China, such as the uncoordinated development of cities and their factors and low efficiency of resource allocation (Fan et al, 2019;Ji et al, 2020;Lin et al, 2021;Zhang et al, 2022). The study of the economic agglomeration effect of population-land allometric growth found that the current rapid economic development in the YRD is still dominated by land expansion, consistent with the results analyzed by scholars using econometric models , and it also shows a time lag in the economic impact of population-land allometric growth between regions.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…It is vital in promoting coordinated regional development and participating in international cooperation and competition. However, there are still some problems in urban agglomerations in China, such as the uncoordinated development of cities and their factors and low efficiency of resource allocation (Fan et al, 2019;Ji et al, 2020;Lin et al, 2021;Zhang et al, 2022). The study of the economic agglomeration effect of population-land allometric growth found that the current rapid economic development in the YRD is still dominated by land expansion, consistent with the results analyzed by scholars using econometric models , and it also shows a time lag in the economic impact of population-land allometric growth between regions.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%